Mineral Compositions of Herbal Coffees Consumed in Turkey - Sekeroglu, Nazim (Asian Journal of Chemistry, 2012)
Interest in herbal natural products such as wild vegetables, herbal teas, herbs, spices and herbal mixtures for healthy life has been gradually rising in recent times. Because of their probable side effects on human health, some ordinary foods and drinks are also substituted by healthier or less harmful ones. Because of the distinguished aroma and stimulant effects, different coffee products are of the most used drinks all over the world. Because of its secondary metabolites, mainly caffeine, coffee products have recently been restricted for some people suffering some ailments like cardiovascular diseases. These are also addictive drinks and desired by some people regularly. All the coffee species, coffee arabica, coffee robusta etc., are grown in warm climates. In some years, unexpected climatic factors or political problems in coffee producing countries cause fluctuations in market prices and crop supply. For this reason, because of the fact that people could not find coffee kernels, they use some plants similar to coffee naturally grown in surrounding area. Having rich biodiversity in flora and cultural profundity in various regions, Turkey has a great number of traditional food and drink. Terebinth coffee (Pistachia terebinthus L.), black cumin coffee (Nigella sativa L.), carob coffee (Ceratonia siliqua L.), date coffee (Phoenix dactylifera) and gundelia coffee (Gundelia tournefortii) are widely consumed herbal coffees in Turkey. Besides their taste and benefit for health, mineral compositions of them are important for food safety. In the present study, some traditional herbal coffees were evaluated for their mineral compositions. Sixteen different minerals (B, Ca, Cd, Cr, Cu, Fe, K, Mg, Mn, Mo, Na, Ni, P, Pb and S) were detected in the coffee samples. Processed herbal coffees were also compared to their raw materials in terms of mineral compositions.